Financialized territory: the territorial determinations of BNDES disbursements to the sugar-energy sector in Mato Grosso and Mato Grosso do Sul - Brazil - Giannini Borges, Ana Claudia [UNESP]; Souza, Jose Gilberto de [UNESP] (Revues Org, 2019)
The objective of this article is to identify the articulation between the National Bank of Social and Economic Development (BNDES) financing for the sugar-energy sector in Mato Grosso and Mato Grosso do Sul, and the territorial determinations generated from this dynamic of financialization. It is important to emphasize the importance of the antivalue in the logic of accumulation and reproduction. The spatial analysis is also performed for the cities, microregions and mesoregions, considering the planted area, the amount of sugarcane grounded and the number of productive units. It was verified that the largest volume of resources was directed to the state of Mato Grosso do Sul, which presented a larger increase in the planted area with sugarcane, the number of sugar - energy agroindustries, the milling capacity, and in the cultivation area. It is evident that the financing logic of the BNDES has contributed to the growth and development of the sugar-energy sector in the analyzed states and, therefore, to change the form of occupation and use of the land and to accentuate the contradictions in the rural areas of these Brazilian states.
Keywords: Sugar-energy sector; State; Disbursement; BNDES; States of Brazil